2022
DOI: 10.1002/1348-9585.12329
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain and telecommuting in Japan: Influence of work environment quality

Abstract: Objectives This study examined the relationship between frequency of working from home and low back pain (LBP), considering the quality of work environment. Methods The study was based on a cross‐sectional internet‐based survey. Of 33 302 respondents, data from 12 774 desk workers were retained for analysis. We used a 0–10 numerical rating scale to assess LBP. Work environment was assessed using five subjective questions. Mixed‐effects logistic regression nested by city… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…All studies were published during and after 2020, and only one study used data from before the COVID-19 pandemic [ 12 ]. There was a relatively good representation of countries throughout the world, with most of them coming from Asia [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and Europe [ 12 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], and some from America and Australia [ 35 , 36 , 37 , 38 , 39 , 40 ]. Only three studies did not have a cross-sectional design: the first was a before/after study [ 28 ], the second was a prospective cohort [ 37 ], and the last was an interventional study [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies were published during and after 2020, and only one study used data from before the COVID-19 pandemic [ 12 ]. There was a relatively good representation of countries throughout the world, with most of them coming from Asia [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and Europe [ 12 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], and some from America and Australia [ 35 , 36 , 37 , 38 , 39 , 40 ]. Only three studies did not have a cross-sectional design: the first was a before/after study [ 28 ], the second was a prospective cohort [ 37 ], and the last was an interventional study [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study focused on participants already suffering from low back pain before implementation of telework [ 30 ], whereas others studies excluded participants with a history of MSK disorders or serious medical conditions [ 19 , 23 , 25 , 28 , 29 , 37 ]. The number of participants varied, ranging from 40 [ 19 ] to 12,774 [ 20 ]. Validated questionnaires were used in almost half of the studies included [ 17 , 18 , 19 , 28 , 29 , 31 , 34 , 35 , 37 , 38 ], with the most used one being the Nordic musculoskeletal questionnaire.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that the mere migration to telework at the beginning of the COVID-19 pandemic exerted no effect on the intensity of neck pain among the participants but that the greater intensity of this pain was related to worse ergonomic conditions of the home workstation, the number of hours working in the computer, and fewer breaks during the workday 10 . In the same sense, other studies pointed out that the musculoskeletal complaints among teleworkers were mediated by inadequate ergonomic conditions and were related to the intensity of telework (days per week of telework) only when the telework conditions were deficient, such as lack of a home workplace where the employees could concentrate for work 22,24–26 …”
Section: Discussionmentioning
confidence: 99%
“… 10 In the same sense, other studies pointed out that the musculoskeletal complaints among teleworkers were mediated by inadequate ergonomic conditions and were related to the intensity of telework (days per week of telework) only when the telework conditions were deficient, such as lack of a home workplace where the employees could concentrate for work. 22 , 24 26 …”
Section: Discussionmentioning
confidence: 99%